2012
DOI: 10.1017/cbo9781139105842
|View full text |Cite
|
Sign up to set email alerts
|

Thomas Jefferson and American Nationhood

Abstract: pages cm.-(Cambridge studies on the American South) includes bibliographical references and index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thomas Jefferson and James Madison, both Founding Fathers and Presidents of the United States, were careful to establish the United States as a republic, a representative form of government, rather than a direct democracy, which they feared could lead to the tyranny of the majority. This is one reason why they helped design a system of checks and balances among the three branches of government (Sheehan, 2009;Steele, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thomas Jefferson and James Madison, both Founding Fathers and Presidents of the United States, were careful to establish the United States as a republic, a representative form of government, rather than a direct democracy, which they feared could lead to the tyranny of the majority. This is one reason why they helped design a system of checks and balances among the three branches of government (Sheehan, 2009;Steele, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some accounts, going all the way back to Charles Beard´s famous study (Beard [1913]), have suggested that there were clear capitalistic and bourgeois self‐interested underpinnings to these ideas, while others have stressed the more traditional (pre‐capitalist) values embodied in them (Kramnick ). However, the fact that this discourse was first and foremost national (Greenfeld ; Steel ) is perhaps more important, at least for the purpose of this article. In addition, a common trait of this thought is that ownership of land gave individuals freedom and power.…”
Section: The Propertied Preconditions For the Emergence Of Nationalismentioning
confidence: 99%
“…Robert F. Sayre (Wisconsin: The University of Wisconsin Press, 1999), 27. 566 Onuf 1987, 7;Steele 2012, 99-100. 567 Jefferson 1952, 604.…”
Section: Introductionmentioning
confidence: 99%